Fintech Payment, Lifestyle, dan Pembelajaran Akuntansi Berpengaruh Terhadap Peengelolaan Keuangan Pribadi Mahasiswa Akuntansi - Nisa, Lutfiatul Khoirun; Zuraidah, Zuraidah (Universitas Gorontalo, 2024)
This purpose of research is to evaluate how fintech payment, lifestyle, and accounting learning affect the way a student majoring in accounting at the State Islamic UIN Maliki Malang manages his finances. This study uses a quantitative approach research method by using primary data collected from questionnaires distributed to university students. The sample of this research consists of 81 students selected by purposive sampling method from a population of 419 students majoring in Accounting, Faculty of Economics, UIN Maliki Malang. The results of the data obtained were evaluated using the SmartPLS version 4.1 application analysis method. Analysis of the results illustrates that fintech payment, lifestyle, and accounting knowledge positively and significantly affect students' personal financial management. In particular, fintech payment and lifestyle have a significant influence on personal financial management, as well as accounting learning.